دراسة ظاهرة تركّز الإجهادات في عمود نقل الحركة(P.T.O) بين الجرّار وآلة الحراثة ورفع موثوقيته على ىمتانة التعب بمساعدة الحاسوب (تطبيق على جرار(Universal 445)) - خضر خفيف; سليمان علي; منهل خريمة (Tishreen University, 2019)
يتناول هذا البحث دراسة ظاهرة انهيار التعب لعمود نقل الحركة بين الجرار وآلة الحراثة. إذ أن الآخاديد الموجودة على العمود والمخصصة لنقل العزوم والحركة، هي مناطق تركز إجهادات تسهم بشكل كبير في انهيار المادة على التعب. الفحص البصري لمقطع التحطم للعمود يظهر شقوق ابتدأت عند جذر الآخاديد، ومن هنا تأتي أهميّة دراسة هذه الآخاديد وتصميمها بعناية فائقة، وهذا ما توفّره البرامج الحسابية والتصميمية باستخدام الحاسوب، إذ سيتم تصميم العمود وربطه بمجموعة من المعادلات والقيم، للتمكن من تغيير جملة من الأبعاد الهندسية بشكل سريع وقت الضرورة، واستخدام طريقة العناصر المنتهية في تحليل الإجهادات للوصول إلى تحديد الإجهادات الأعظمية، وبالتالي المناطق الخطرة باستخدام برنامج التصميم الميكانيكي  KCAD/CATIAوصولاً لحالة التصميم المثالية. إذ تعتمد الطريقة التحليلية على فرضيات المتانة لتحديد الإجهادات المؤدية لفشل العمود، ومعرفة أبعاد العمود الضرورية بالمقارنة مع الإجهادات المسموحة. نستخدم أيضأ طريقة قانون Basquin's power في حساب عدد مرات التحميل .وقد وجد أن تغيير حالة تصميم العمود القائمة إلى حالة تصميم العمود المثالية المستنتجة في نهاية البحث (L1= 90mm، = 70mm، Z= 8،= 10mm ، Ld =2.199mm)، أعطى نتائج أفضل بنسبة %50 .   This search deals with studying the phenomenon of the fatigue of failure at transmission shaft between the tractor and tillage machine. Where the splines existed onto shaft and specified for transmission of moments and movement is stresses concentration regions contributes efficiently in failure of material on the fatigue. Visual examination of the fractured shaft surface clearly showed cracks initiated from roots of splines. Hence the importance of studying these splines and designed them fussily and this is availability design and arithmetical  software aided computer, where they will be designing  the  shaft and associated with group from equations and relations to be able to change sentence from geometric dimensions quickly necessity time, and use the finite elements method in analysis of stresses to reach the determine the maximum stresses, and therefore perilous regions by used CAD/CATIA mechanical design program for arrivals into ideal design state. Where analytical approach based on durability criteria for determine  stresses leading to failure of shaft and therefore necessary to know shaft of dimensions compared with allowable stresses. We also use Basquins power law in calculated of loading cycles numbers. It was found that changing the state of the natural shaft design to the state of the ideal shaft design derived in the end of the research gave better results by 50%.